Acid sensing ion channels in rat cerebral arteries: probing the expression pattern and vasomotor activity - Akanji, Oluwadamilola; Weinzierl, Nina; Schubert, Rudolf; Schilling, Lothar (Life sciences, 2019)
Aims - The recent identification of acid sensing ion channels (ASICs) in vascular beds suggests their possible involvement in modulating vasomotor tone. Therefore, we investigated the gene expression profiles of ASIC subtypes in the middle cerebral artery (MCA) of Wistar rats and the functional implication of ASICs in acidosis-induced relaxation as well as maintenance of resting tension. - Main methods - Real time PCR was employed to study the pattern of ASIC mRNA expression in the MCA wall in comparison with (i) matching brain tissue samples and (ii) arteries cultured for 24h and 48h. The functional implication regarding vasomotor response to acidosis and maintenance of resting tension was assessed using in vitro myography. - Key findings - A robust mRNA expression of ASIC-1, -2 and -4 was found in brain tissue samples and to a lower extent in freshly isolated MCA. In the MCA wall, short term culture induced a down-regulation of ASIC-1 and -2 expression without any remarkable change in ASIC-4 expression. Acidosis induced a pH-related relaxation of freshly isolated MCA ring segments, being more pronounced after short term culture. Incubation with the ASIC blocker amiloride moderately enhanced acidosis-induced relaxation, in cultured MCAs somewhat stronger than in freshly isolated vessels. In addition, amiloride resulted in a decrease of resting tension, albeit only in freshly isolated MCA. - Significance - Our results comprehensively describe ASIC subtype composition in the rat MCA in physiological and pathological conditions and strongly suggest the involvement of ASICs in the modulation of vasomotor responses under conditions of normal or decreased pH values.